Rentabilité technique et cycles en assurance I.A.R.D. au Canada - Outreville, J.-François (Assurances, 1986)
The underwriting cycle has been the subject of much recent discussion in the insurance industry. The typical explanation is that this cycle, if indeed it exists, is a supply-side phenomenon. The purpose of this paper is to provide some measure of this cycle for the Canadian market and to show that variables usually considered to explain these fluctuations are not significant in this market.